2021
DOI: 10.3390/cells10010154
|View full text |Cite
|
Sign up to set email alerts
|

GRKs and Epac1 Interaction in Cardiac Remodeling and Heart Failure

Abstract: β-adrenergic receptors (β-ARs) play a major role in the physiological regulation of cardiac function through signaling routes tightly controlled by G protein-coupled receptor kinases (GRKs). Although the acute stimulation of β-ARs and the subsequent production of cyclic AMP (cAMP) have beneficial effects on cardiac function, chronic stimulation of β-ARs as observed under sympathetic overdrive promotes the development of pathological cardiac remodeling and heart failure (HF), a leading cause of mortality worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…At present, GRKs are comprising seven isoforms (GRK1-7) in vertebrates. More importantly, GRK2 and 3 isoforms, the second subfamily named β-adrenergic receptor kinase subfamily, are ubiquitously expressed and generally localized to the cytosol and plasma membrane ( 14 ). Furthermore, recent studies have found that there are diverse changes in the expression and activity levels of GRK2 under pathophysiology conditions.…”
Section: Regulation Of Grk2 Activity Under Pathophysiology Conditionsmentioning
confidence: 99%
“…At present, GRKs are comprising seven isoforms (GRK1-7) in vertebrates. More importantly, GRK2 and 3 isoforms, the second subfamily named β-adrenergic receptor kinase subfamily, are ubiquitously expressed and generally localized to the cytosol and plasma membrane ( 14 ). Furthermore, recent studies have found that there are diverse changes in the expression and activity levels of GRK2 under pathophysiology conditions.…”
Section: Regulation Of Grk2 Activity Under Pathophysiology Conditionsmentioning
confidence: 99%
“…This raises the question of the source of cAMP during viral infection. A possible explanation would be that virus entry could increase the pool of cAMP via the soluble adenyl cyclase (AC) which has been previously shown to regulate EPAC1 activation and endocytosis [ 22 , 23 , 24 ]. Consistently, it is suggested that soluble AC promotes endocytic pathway of viral entry by stimulating vacuolar ATPase-dependent acidification of endosomes and lysosomes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot determine whether the activity of both toxins have a direct effect on the ß1 adrenergic and ß2 adrenergic receptors, both linked to increased chronotropism and inotropism of the cardiac muscle. These actions are due to the stimulating action on Protein G, which increases adenyl cyclase activity, causing high levels of cyclic AMP (34)(35)(36)(37). Gibbins (38) has suggested that the principal factor to take in consideration about the cardiotoxic effect has been the modulation of heart frequency that can be regularly measured by a direct optical examination, by video-edge detection systems.…”
Section: Discussionmentioning
confidence: 99%